Teaching Game Programming in Family Workshops. - von Wangenheim, Christiane Gresse; von Wangenheim, Aldo (Computer (00189162), 2014)
An initiative in Brazil teaches computing to young people alongside their parents in family workshops through game programming using Scratch--with benefits that reach beyond the classroom and into the community.